2012
DOI: 10.1136/bmj.e372
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors and risk of hip fracture in relation to dietary and lifestyle factors: a prospective cohort study

Abstract: Objective To examine the association between chronic use of proton pump inhibitors (PPIs) and risk of hip fracture.Design Prospective cohort study.Setting Nurses' Health Study, which originally recruited from the 11 most populous states in the US.Participants 79 899 postmenopausal women enrolled in the Nurses' Health Study who provided data on the use of PPIs and other risk factors biennially since 2000 and were followed up to 1 June 2008. Main outcome measure Incident hip fractureResults During 565 786 person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
118
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(127 citation statements)
references
References 41 publications
2
118
1
6
Order By: Relevance
“…• The infections, particularly, the bacterial pneumopathies [24] and the intestinal infections, especially to Clostridium difficilae [25] • Osteoporotic fractures [26,27] • On the other hand, medicines decreasing the acid gastric secretion such as the long-term PPI would be theoretically capable of leading the genesis of gastric tumors, and even colorectal; in fact, the hypergastrinemia is led by these treatments [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…• The infections, particularly, the bacterial pneumopathies [24] and the intestinal infections, especially to Clostridium difficilae [25] • Osteoporotic fractures [26,27] • On the other hand, medicines decreasing the acid gastric secretion such as the long-term PPI would be theoretically capable of leading the genesis of gastric tumors, and even colorectal; in fact, the hypergastrinemia is led by these treatments [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some confounding variables, that may bias results, are present. [89][90][91][92] Of note, PPIs use is associated with greater than 50% increase in fracture risk among current and former smokers; in contrast, there is no association among women who never smoked. 89 The results of other studies are different.…”
Section: Osteopenia Osteoporosis and Risk Of Bone Fracturementioning
confidence: 99%
“…Bone fractures have also been linked in several observational studies (27). A crossover study analyzed bone mineral density of the hip and lumbar vertebrae, and it showed no association between PPI use and osteoporosis (28).…”
Section: Overuse and Its Consequencesmentioning
confidence: 99%